Stosunek dydaktyki literatury do teorii pedagogicznych w okresie dwudziestolecia międzywojennego: zagadnienia wybrane = Didactics of Literature in Relation to Pedagogical Theories During a Twenty Year Period Between the Two Worldwars - Kujawska, Krystyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The work shows some relations between the then arising didactics of literature and different pedagogical trends which gained shape at the end of the XIX century and the beginning of the XX century. It shows an inspiration to modern education and above of all the impact of work and arts, emerging from discussions about the contents of teaching and methods and forms of studies of a piece of literary work.
Keywords: dydaktyka literatury; teoria pedagogiczna; 1918-1939